PERSONALIZED LEARNING MATERIALS: DEVELOPING MATERIALS FOR DIFFERENTIAL LEARNING IN GROUPS OF DIFFERENT LEVELS (International journal of artificial intelligence, 2024)
The article analyzes the importance and methods of developing personalized educational materials in the process of differential education for groups of different levels. Special methodological approaches are proposed for the effective organization of the educational process, taking into account the individual characteristics, knowledge levels and interests of students. This article provides practical recommendations for educators and educational institutions on increasing the level of student learning through a personalized approach. Also, the directions of adapting educational materials and improving the pedagogical skills of teachers using innovative technologies are considered.